Survival after laparoscopy versus laparotomy for apparent early-stage uterine clear cell carcinoma: Results of a large multicenter cohort study - Shui, Chengyu; Ran, Lin; Tian, Yong; Qin, Li; Gu, Xin; Xu, Hui; Hu, Cui; Zhang, Lin-Lin; Xu, You; Cheng, Chen; Huan, Wu (Frontiers in Oncology, 2022)
Objective To compare the long-term survival between laparoscopic surgery and open surgery in patients with apparent early-stage uterine clear cell carcinoma (UCCC). Patients and methods 254 patients with apparent early-stage UCCC were reviewed. Comparisons were made between patients who underwent laparoscopic surgery versus those who underwent open surgery. Baseline data, clinicopathological data, and oncological outcomes were analyzed. 5-year disease-free survival (DFS) rate and 5-year overall survival (OS) rate were estimated and compared using the Kaplan-Meier method and the Log-rank test. The Cox proportional hazard regression model was employed to control the confounding factors. Results 147 patients underwent laparoscopic surgery, and 107 patients were managed by open surgery. No differences in terms of recurrence rate (laparoscopy versus laparotomy: 10.9% versus 12.9%, P=0.842) and recurrence pattern were observed. For patients who underwent open surgery and patients who underwent laparoscopic surgery, the 5-year DFS rates and 5-year OS rate were 75.8% (95% CI: 65.8%-83.2%) and 69.1% (95% CI: 58.8%-77.4%), 66.0% (95% CI: 57.1%-73.5%) and 60.8% (95% CI: 52.0%-68.5%), respectively. The Cox proportional hazards regression model shown that for apparent early-stage UCCC, the approach of surgical staging was not an independent predictor for survival (laparoscopy versus laparotomy: for DFS, aHR=1.06, 95% CI=0.64-1.75, P=0.826; for OS, aHR=1.10, 95% CI=0.72-1.68, P=0.671). Conclusion For apparent early-stage UCCC, in terms of oncological survival, laparoscopic surgery was as safe as open surgery.